2019
DOI: 10.1186/s13643-019-1103-8
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation and mental health among adult forced migrants: a meta-narrative systematic review protocol

Abstract: Background The global refugee crisis has become central to health and policy debates. There is a growing need to investigate how acculturation impacts mental health among asylum seekers and refugees. Many forced migrants have an increased risk of experiencing negative mental health outcomes, but this review will only assess the current literature on acculturation and mental health among adults. Research questions include the following: (1) How is acculturation conceptualised? (2) What are the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
0
5
0
1
Order By: Relevance
“…There may be four possible outcomes of acculturation as defined by Berry (1997): assimilation – completely adopting the new culture and rejecting one’s own culture; separation – distancing from the new culture strongly emphasising the culture of origin; marginalisation – rejecting and/or being excluded from both the original and new culture; and bicultural integration – blending/balancing both the original culture and new culture. Studies investigating the resettlement or post-migration experiences of refugees from all backgrounds have found that acculturation is one of the most common and greatest challenges (Bertram et al., 2014; Chung et al., 2000; Cuéllar, 2000; Mengistu & Manolova, 2019).…”
Section: Acculturation Integration and Transculturationmentioning
confidence: 99%
“…There may be four possible outcomes of acculturation as defined by Berry (1997): assimilation – completely adopting the new culture and rejecting one’s own culture; separation – distancing from the new culture strongly emphasising the culture of origin; marginalisation – rejecting and/or being excluded from both the original and new culture; and bicultural integration – blending/balancing both the original culture and new culture. Studies investigating the resettlement or post-migration experiences of refugees from all backgrounds have found that acculturation is one of the most common and greatest challenges (Bertram et al., 2014; Chung et al., 2000; Cuéllar, 2000; Mengistu & Manolova, 2019).…”
Section: Acculturation Integration and Transculturationmentioning
confidence: 99%
“…Furthermore, culture itself has been identified as an influential SDoH, and being denied the opportunity to engage in cultural practices has been identified as a major public health concern, particularly for migrant women, due to the negative health ramifications it can have in the long term [51]. However, it has been identified to be particularly complex in forced migrants (including refugee populations) due to the concept of involuntary migration [52]. Developing a greater understanding of the relationship between acculturation and mental health among forced migrants can be identified as paramount due to the unprecedented number of individuals of refugee background worldwide [5].…”
Section: Discussionmentioning
confidence: 99%
“…Developing a greater understanding of the relationship between acculturation and mental health among forced migrants can be identified as paramount due to the unprecedented number of individuals of refugee background worldwide [5]. Unfortunately, there is a lack of literature investigating the topic, as it is currently uncertain whether the large body of research investigating accul-turation and mental health in immigrants and racial and ethnic monitories is comparable for forced migrants [52]. Investigating this further will allow the development of more progressive government policies which protect the cultural values, practices and beliefs of newly arrived immigrants and forced migrants.…”
Section: Discussionmentioning
confidence: 99%
“…Within the various theoretical frameworks, the relationship between acculturation and health has been studied for decades [15][16][17]. Acculturation has been proven to influence health through healthy behaviors, access to healthcare services, social support, self-esteem, and stress [12,18,19]. Most empirical studies using a unidimensional model have consistently found that nondominant groups with low acculturation are more likely to have general health issues [20] and diabetes [21,22].…”
Section: Introductionmentioning
confidence: 99%